Association between night-shift work, sleep quality and metabolic syndrome. Issue 10 (21st July 2018) - Lim, Yin Cheng; Hoe, Victor C W; Darus, Azlan; Bhoo-Pathy, Nirmala
Abstract : Objectives: Occupational factors, particularly night-shift work, are attracting growing interest as a possible determinant of metabolic syndrome (MetS). This study aimed to determine the association between night-shift work and MetS, and assess whether sleep quality is a mediating factor. Methods: A cross-sectional study was conducted among Malaysian manufacturing workers, aged 40–65 years old. They completed a self-administered questionnaire on sociodemographics, lifestyle and family history, and the Pittsburgh Sleep Quality Index (PSQI) questionnaire. Waist circumference, blood pressure, fasting blood sugar, triglycerides and high-density lipoprotein levels were measured. Baron and Kenny's method, Sobel test and multiple mediation models with bootstrapping were used to determine whether the PSQI global score or its components mediated the association between night-shift work and MetS. Results: Of the 494 participants, 177 (36%) worked night shift and 51% were men. The prevalence of MetS was 37%. Night-shift work was independently associated with a twofold increase in the risk of MetS (adjusted OR: 1.92, 95% CI 1.24 to 2.97). However, the association between night-shift work and MetS did not appear to be modified by sex. Night-shift workers also reported significantly poorer sleep quality, longer sleep latency, shorter sleep duration, sleep disturbances and daytime dysfunction. Robust mediation analysis nonetheless showed that neither PSQI global score nor its components mediated the association between night-shift work and MetS. Conclusion: Early screening and management of MetS and the development of programmes to improve sleep quality should be carried out among night-shift workers. Future research should investigate other modifiable mediators linking night-shift work and MetS.